Numerical simulation of KdV equation by finite difference method - Yokus, A.; Bulut, H. (Indian Assoc Cultivation Science, 2018)
In this study, the numerical solutions to the KdV equation with dual power nonlinearity by using the finite difference method are obtained. Discretize equation is presented in the form of finite difference operators. The numerical solutions are secured via the analytical solution to the KdV equation with dual power nonlinearity which is present in the literature. Through the Fourier-Von Neumann technique and linear stable, we have seen that the FDM is stable. Accuracy of the method is analyzed via the norm errors. The numerical, exact approximations and absolute error are presented in tables. We compare the numerical solutions with the exact solutions and this comparison is supported with the graphic plots. Under the choice of suitable values of parameters, the 2D and 3D surfaces for the used analytical solution are plotted.
Keywords: KdV equation; Finite difference method; Linear stability; Numerical solution; 02; 60; -x; 02; 60; Cb; 02; 30; Jr